Faktor-Faktor Yang Mempengaruhi Cash Holding Pada Perusahaan Consumer Non-Cyclicals - Supra, Edvandi Fam; Nugroho, Vidyarto (Fakultas Ekonomi, Universitas Tarumanagara, 2025)
This study aims to obtain empirical evidence regarding the effect of profitability, leverage, firm size, and growth opportunity on cash holding in consumer non-cyclicals companies. The sampling technique used was purposive sampling. The sample data in this study were 120 sample data. This study uses secondary data that is processed using IBM SPSS version 22. The results of the F test show that profitability, leverage, firm size, and growth opportunity together have a significant effect on cash holding. The results of the t test show that profitability had a positive and significant effect on cash holding, while leverage has a negative and significant effect on cash holding. Firm size has a positive and insignificant effect on cash holding and growth opportunity has a negative and insignificant effect on cash holding.